Experimental study on deflagration characteristics of non-uniform oil mist in an enclosed chamber - Jia Jia; Guoying Yao; Qian Li; Jie Xu; Shouxiang Lu (Case Studies in Thermal Engineering, 2023)
The deflagration characteristics of oil mist in the marine enclosed chamber are studied. The results show that oil mist deflagration in a non-uniform enclosed chamber is a violent process. When the nozzle size is 1.0 mm, the maximum oil mist deflagration overpressure in the chamber can reach 0.945 MPa. Increasing the nozzle size strengthens the deflagration intensity of oil mist. As the nozzle size increases, the oil mist deflagration flame propagation velocity, peak deflagration overpressure, and gas temperature increase. In addition, the oil mist deflagration process is facilitated by the increase in injection pressure. The maximum flame propagation velocity and maximum deflagration overpressure gradually improve with the increase in injection pressure. This is mainly because the increase in injection pressure leads to better atomization of oil mist droplets, increasing surface area of the oil mist, and the increase in oil mist concentration, which makes the intensity of oil mist deflagration in the enclosed chamber more intense. Nozzle size on the intensity of oil mist deflagration is more influential than the injection pressure.